Improving Learning and Developing Professional Judgment in Large Classes Through Collaboration and Self and Peer Assessment. - Willey, Keith (Office for Learning and Teaching, 2014)
Final report of a Teaching Fellowship at the University of Technology, Sydney. The fellowship focussed on, and assisted academics to, adopt, design, and implement collaborative learning-oriented activities incorporating the innovative use of self and peer assessment. In addition, a secondary focus was on assisting academics to improve the quality of grading and feedback provided to students and to develop, construct and maintain academic standards. A combination of workshops, presentations and individual support and resources were provided to disseminate and adapt tested practices to individual contexts. Particular emphasis was placed on the use of SPARKPLUS, a tool that facilitates self and peer assessment and provides feedback on an individual's contribution to a team project, individual work or enables participants to benchmark their judgment and reasoning against their peers and/or an expert instructor.